Bio-climate and Plant Introduction in Dry Zone - Seth, S. K.; Khan, M. A. Waheed (Indian Forester, 1959)
The study of climate and climatic homologues is an essential prerequisite in any scheme of plant introduction. This is particularly so for afforestation practices in the dry zone. The broad principles relating to influence of climate on the distribution of plants are reviewed and Emberger's climatic index is worked out for the dry zone of India in order to delimit climatic sub-types. It is, however, felt that the sub-types so formed do not harmonise with the natural vegetation types of the area. The concept of "Effective Temperature Index" is therefore developed which sufficiently modifies Emberger's formula to bring it in consonance with the natural vegetation types. Instead of plotting Q, the bioc1imatic value (200P/M2-m2) against m(av. min. temp. of the coldest month), it is plotted against m( M-m) where M is the av. max. temp. of the hottest month.